Atopy and common warts. - Jemec, G.B.E.; Moe, A.T.T.; Juel Henningsen, S. (European Journal of Pediatric Dermatology, 2018)
Atopy is thought to be a predisposing factor for common warts. The atopic disposition in patients presenting at a private clinic for the treatment of common warts was studied using a standardised questionnaire suggested for studies of atopic dermatitis. Patients with common plantar warts had a similar score to that of negative controls, while both these groups had significantly lower score than patients undergoing treatment for atopic dermatitis. The data support previous epidemiological studies suggesting that atopy is not a predisposing factor for common warts.